A study on analyzing the Non Performing Asset (NPA) level in Tripura Gramin Bank - et. al., Sentulal Debbarma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The banking sector is a backbone of any developing countries. The RBI and other regulatory bodies in India have taken several policies to improve the functioning of the banks. It is therefore important that the banks deal efficiently with their credit policy. The interest earned from the advances made by the banks is the main income to the banks. The health of the bank is decided by the amount of Non Performing Assets (NPA) level. As it is a performance indicator to the banks, the NPA have direct impact on the profitability, liquidity and solvency position. The higher NPA is a sign of inefficiency of the banks and so the NPAs are to be controlled. In this paper the researcher highlights the trend of the Tripura Gramin Bank (TGB), the factors leading to increase in NPA and suggestion to curve the menace of the NPA.